2023
DOI: 10.1126/sciadv.adg8156
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy restricts BAX/BAK-independent, Parkin-mediated apoptosis

Abstract: Degradation of defective mitochondria is an essential process to maintain cellular homeostasis and it is strictly regulated by the ubiquitin-proteasome system (UPS) and lysosomal activities. Here, using genome-wide CRISPR and small interference RNA screens, we identified a critical contribution of the lysosomal system in controlling aberrant induction of apoptosis following mitochondrial damage. After treatment with mitochondrial toxins, activation of the PINK1-Parkin axis triggered a BAX- and BAK-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…During mitochondrial stress, there exists a continual competition between mitophagy and the possible release of Cytochrome c. Effective elimination of damaged mitochondria through mitophagy plays a crucial role in determining the outcome. A recent study has indeed shown that PINK-Parkin-induced proteasome-dependent rupture of the OMM can lead to the release of Cytochrome c when mitochondria are not adequately cleared through autophagic processes 38 . From our present findings, it appears that in situations where cellular autophagy mechanisms are active, the establishment of the VDAC1-PHB2 complex and the efficient exposure of PHB2 may have the potential to promote cell survival by facilitating mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…During mitochondrial stress, there exists a continual competition between mitophagy and the possible release of Cytochrome c. Effective elimination of damaged mitochondria through mitophagy plays a crucial role in determining the outcome. A recent study has indeed shown that PINK-Parkin-induced proteasome-dependent rupture of the OMM can lead to the release of Cytochrome c when mitochondria are not adequately cleared through autophagic processes 38 . From our present findings, it appears that in situations where cellular autophagy mechanisms are active, the establishment of the VDAC1-PHB2 complex and the efficient exposure of PHB2 may have the potential to promote cell survival by facilitating mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been proposed in the literature that following mitochondrial damage, cardiolipin is externalised to the outer mitochondrial membrane where it can be recognised by LC3 proteins thereby initiating mitochondrial autophagy to remove damaged mitochondria. In particular, oxidised cardiolipin can be specifically recognised by LC3A [ 47 ].The degradation of defective mitochondria is an essential process to maintain cellular homeostasis [ 48 ]. However, there is evidence of defective mitophagy in type 2 diabetic mice, such that damaged mitochondria cannot be cleared in a timely manner [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to distinct stresses, PGAM5 dephosphorylates BCL-XL to inhibit apoptosis or FUNDC1 to enhance mitophagy by switching between dimeric and multimeric states [ 282 ]. Surprisingly, in the absence of mitophagy, PINK1/Parkin can promote cell apoptosis through a non-BAX pathway [ 283 ]. The ubiquitination effect of UPS on OMM promotes the release of cytochrome C, directly activates autophagy receptors, upregulates mitophagy, and inhibits apoptosis [ 283 ].…”
Section: Physiological Roles Of Mqcmentioning
confidence: 99%
“…Surprisingly, in the absence of mitophagy, PINK1/Parkin can promote cell apoptosis through a non-BAX pathway [ 283 ]. The ubiquitination effect of UPS on OMM promotes the release of cytochrome C, directly activates autophagy receptors, upregulates mitophagy, and inhibits apoptosis [ 283 ].…”
Section: Physiological Roles Of Mqcmentioning
confidence: 99%